BYNAMES IN ENGLISH AND KURDISH: A SOCIO-CULTURAL STUDY - KHUDHIR , HASHIM T.; SALO, IBRAHIM K. (Journal of Duhok University, 2020)
ABSTRACT Bynames as supplementary names have been the products of society and culture at a time when personal names were insufficient to identify people who shared identical personal names in society. This study therefore aims to investigate English and Kurdish bynames in the perspective of society and culture by giving emphasis to similarities and differences between them. In obtaining certain results related to socio-cultural aspects of bynames, this study has investigated the derived sources of English and Kurdish nicknames, and the reasons behind bynames coinage and the intentions of using them in Kurdish. In this study, English data were based on books, journal articles, and websites while Kurdish data were collected from books, websites, interviews, and a questionnaire. Using descriptive analysis, this study investigated English and Kurdish bynames in terms of society and culture. The results have revealed that the majority of English nicknames tended to be derived from nouns whilst the largest portion of Kurdish nicknames were found to be sourced from adjectives. This implies that based on his/her socio-cultural background, the nickname coiner skillfully manipulates these parts of speech (nouns, adjectives, verbs, compounds) in the garment of nicknames to send society his/her core message about the nicknamed. The results have also showed that the social function of the majority of bynames that pertain to male and female byname bearers in Kurdish can be an affectionate function and can mainly be used for fun by byname users. This means that bynames in Kurdish serve the function of showing love and affinity and these bynames can thus be used humorously. This can be added that Kurdish culture is behind promoting the beliefs of byname coinage and usage by Kurdish byname coiners and users.